Relationship of the stretch-shortening cycle to sprint performance in trained female athletes - Hennessy, L.; Kilty, J. (The Journal of Strength and Conditioning Research, 2001)
This study assessed the relationship of long and short stretch-shortening cycle test scores to sprint performances in trained female athletes. Seventeen trained, female, high school, competitive sprinters completed the following tests: countermovement jump for vertical distance (CMJ), bounce drop jump for height with minimum ground contact time (BDJ index), and ground contact time (GCT) during the BDJ and a 5-step bound (5B) test. Group mean and SD values were as follows: height, 167.7 ± 3.7 cm; body mass, 59.9 ± 7.2 kg; and percentage of body fat (PF), 20.3 ± 1.8%. Sprint performances at 30-, 100-, and 300-m distances were assessed. Stretch-shortening cycle performance and sprint results (mean ± SD) were as follows: CMJ, 33.8 ± 3.8 cm; BDJ index, 166.7 ± 24.7 cm/s; 5B test, 10.98 ± 0.76 m; 30-m sprint, 4.58 ± 0.17 seconds; 100-m sprint, 12.9 ± 0.61 seconds; and 300-m sprint, 45.03 ± 2.94 seconds. Correlations indicated that no relationship existed between PF and the dependent sprint variables. Significant correlations (p < 0.05) existed between CMJ and 30-m (r = 0.60), 100-m (r = 0.64), and 300-m (r = -0.55) sprint times; BDJ index and 30-m (r = 0.79) and 100-m (r = 0.75) sprint times; and 5B test and 300-m sprint time (r = -0.54). Multiple regression analysis found significant T values for BDJ index with 30- and 100-m sprints and CMJ and PF with 300 m. Results indicated that the BDJ index and CMJ tests were significantly related to sprint performances in female athletes.